Concussion is associated with altered preparatory postural adjustments during gait initiation. Issue 11 (25th May 2017) - Doherty, C; Ryan, John; Komaba, Yusuke; Inomata, Akihiro; Zhao, Liang; Caulfield, Brian
Abstract : Objective: To quantify the preparatory postural adjustments (PPAs) during gait initiation (GI) in a group with concussion compared with a 'healthy' control group. Design: Case-control study Setting: University Biomechanics Laboratory. Outcome measures: Centre of pressure (COP) trajectory computed from a force plate and centre of mass (COM) trajectory as computed from an inertial measurement unit placed on the sacrum. Results: Concussed patients exhibited decreased COP excursion in the posterior direction on their dominant foot, both when it was the stepping limb (9.71mm [95% CI: 8 to 11mm] vs 15mm [95%CI: 12 to 17mm]) and when it was the support limb (10mm [95% CI: 8 to 12mm] vs 18mm [95%CI: 14 to 21mm]). This was reflected in the trajectory of the COM, wherein concussion patients exhibited lower posterior displacement (19mm [95%CI: 19.4mm to 19.7mm]) compared with controls (23mm [95%CI: 23 to 24]). Conclusions: : Individuals with concussion display deficits during a GI task comparable to those which have previously been established in populations with supraspinal impairments in motor control. Competing interests: None.